Cicatrizes urbanas: marcas de socialização e formação na cidade em Jataí-GO - SILVA, Sinara Rosa Carvalho e (2009)
This paper discuss the city while mediation in the sociability, formation and education process. It considers that the modern city is puts beyond of the place and of the simple people and object agglomerations, as a way of living and where is the specific form of organization of the space in the cultural system of the capitalist industrial society. From this perspective, we investigate the relationship and educative implications produced by academics of the Pedagogy course of the Federal University of Goiás-Campus Jataí (UFG-CJ), concerning the experience, sociability processes and formation in Jataí, city of Southwest Goiás-Brazil. This work analyzes the relationships between persons and the city of Jataí. The city, space that (dis)arrange contradictorily as fundamental structural reality of the capitalist society is argued from Marx and Engels (2006); Munford (1982); Castells (1983), Cavalcanti (2001), Souza (2003), Rolnik (2004), Santos (1999), Miranda (1995) and Lefebvre (1991). We understand Jataí, in its singularity, as expression of the universality of the present cities, based in Melo (2003) and Silva (2005). One of the features of Jataí, disclosed as universal, is the implantation of the Federal University of Goiás (UFG), expression and consolidation of the necessities that the modernization process caused. This process is discussed based in Dourado (2001). The course of Pedagogy is accented because expressed the consolidation of the Campus in the decade of 1980. This research has an exploratory sense with predominantly qualitative procedures. We employ bibliographical research, questionnaires and interviews. The questionnaires and interviews had allowed to elaborate reflections about the reality of Jataí city, as well as of its habitants and visitors. In the sociability city spaces the persons have a link with the traces of the community, even though alive in an ambiguous context, in which characteristics of the modern society also exists. The citizens speak of itself, but they send to the universality of what it is lived in the city, in Jataí, from what is possible to consider the universality of the today s cities. These are references to understand the development of the concept and the reality of society and individual according to Adorno and Horkheimer (1973a and 1973b), Tönnies (MIRANDA, 1995) and Bourdieu (1997). This paper shows that Jataí is a place where are inscribed the traditional and the modern and such reality makes possible the individual to live the contradiction of to enchant with the place that, at the same time, it appears to him as something strange, in the measure as it passes by transformations. Such ambiguity is put in a process of interaction and tension, and it is lived in all the city spaces, especially in the university, important socialization place of and in the city, in which are reproduced conditions lived in the same one and, as well as in this, the relationships are established in contradiction